Pengaruh Pembiayaan Mudharabah dan Musyarakah terhadap Financing to Deposit Ratio (FDR) pada Bank Umum Syariah di Indonesia - Elya Saputri; Eka Sri Wahyuni; Rizky Hariyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was determine the effect of Mudharabah and Musyarakah Financing on Financing To Deposit Ratio (FDR) at Islamic Commercial Banks in Indonesia in 2020-2022, on a quarterly basis. This study uses quantitative methods using secondary data in the form of quarterly financial reports of Islamic Commercial Banks in 2020-2022. Data analysis using descriptive statistics, classical assumption test, multiple linear regression analysis, t-test, F-test, and coefficient of determination through the IBM SPSS 25. The results revealed that mudharabah financing partially had a significant effect on the Financing To Deposit Ratio (FDR) at Islamic Commercial Banks in Indonesia in 2020-2022. On the other hand, musyarakah financing partially has no significant effect on the Financing To Deposit Ratio (FDR) of Islamic Commercial Banks in Indonesia in 2020-2022. Meanwhile, mudharabah and musyarakah financing simultaneously affect the Financing To Deposit Ratio (FDR) at Islamic Commercial Banks in Indonesia in 2020-2022.